2014
DOI: 10.1002/adem.201400147
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Nano/Sub‐Micron F401 Titanium Alloy

Abstract: Titanium alloys are attractive as structural materials mainly due to their high specific strength and excellent corrosion resistance. Modifying conventional Ti alloys to impart nanostructural features holds promise for improving specific strength without reducing corrosion resistance. This study aimed to evaluate the corrosion behavior of a nano/sub-micron F401 titanium alloy compared to its conventional Ti-6Al-4V counterpart. Following mechanical alloying and extrusion, the microstructure was evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…These diffraction peaks of sample H1 are mainly attributed to the initial α-Ti and (α + β)-Ti phases. It has been reported that a passivation film consisting mainly of TiO 2 forms on the surface of the titanium alloy during the salt spray exposure [20,25]. As shown in Figure 5c, the Ti2p 3/2 and Ti2p 1/2 peaks in sample H1 locate at 458.48 and 464.17 eV, respectively, which correspond to the Ti-O binding state, confirming the formation of a thin TiO 2 passivation film [26].…”
Section: Figure 3 Displays the Corrosion Kinetic Curves Of All Tested...supporting
confidence: 52%
See 1 more Smart Citation
“…These diffraction peaks of sample H1 are mainly attributed to the initial α-Ti and (α + β)-Ti phases. It has been reported that a passivation film consisting mainly of TiO 2 forms on the surface of the titanium alloy during the salt spray exposure [20,25]. As shown in Figure 5c, the Ti2p 3/2 and Ti2p 1/2 peaks in sample H1 locate at 458.48 and 464.17 eV, respectively, which correspond to the Ti-O binding state, confirming the formation of a thin TiO 2 passivation film [26].…”
Section: Figure 3 Displays the Corrosion Kinetic Curves Of All Tested...supporting
confidence: 52%
“…Obviously, the Cl 2 acts as a key carrier, accelerating the degradation reaction of the substrate, and results in the rapid growth of the oxide layer. As identified by the SEM image of Figure 8c, the continuous volatilization of chloride and the significant structure differences of these oxides trigger high thermomechanical growth stress, which eventually results in a severe layered separation and local cracking [36] since the coefficients of thermal expansion of TiO 2 , Al 2 O 3 , and Ti6Al4V alloy are 8.2 × 10 −6 , 8.1 × 10 −6 , and 10~12 × 10 −6 K −1 , respectively [25]. Therefore, the significant difference in thermal expansion coefficients between the oxide layer and substrate eventually induces the initiation of surface ring breaking [37].…”
Section: Ti + O2 = Tio2mentioning
confidence: 99%
“…Degradation behavior of a wide range of materials has been investigated . Stainless steels are often used as structural material in the corrosive environment due to their ability to form stable passive layer .…”
Section: Introductionmentioning
confidence: 99%